N-(2-Oxo-2H-chromen-3-yl)benzamide - Jotani, M.M.; Baldaniya, B.B.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The phenyl ring in title molecule, C(16)H(11)NO(3), forms a dihedral angle of 7.69 (6)degrees with the fused ring system. The observed conformation is stabilized by intramolecular N-H center dot center dot center dot O and C-H center dot center dot center dot O interactions. In the crystal, supramolecular chains are formed along the b axis which are mediated by pi-pi interactions [centroid-centroid distance = 3.614 (2) angstrom].